On following pages: 25. Long-finned Pilot Whale (Globicephala melas); 26. Short-finned Pilot Whale (Globicephala macrorhynchus); 27. Pygmy Killer Whale (Feresa attenuata); 28. Risso's Dolphin (Grampus griseus); 29. Melon- in Delphinidae - Russell A. Mittermeier; Don E. Wilson (IAES International Journal of Artificial Intelligence (IJ-AI), 2014)
On following pages: 25. Long-finned Pilot Whale (Globicephala melas); 26. Short-finned Pilot Whale (Globicephala macrorhynchus); 27. Pygmy Killer Whale (Feresa attenuata); 28. Risso's Dolphin (Grampus griseus); 29. Melon- Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 515, DOI: 10.5281/zenodo.6610922